PARTISIPASI PEMILIH PEMULA MAHASISWA FAKULTAS HUKUM UNIVERSITAS ATMA JAYA YOGYAKARTA DALAM PEMILU TAHUN 2014 - Yohanes Hartono, Dewi Krisna Hardjanti, (Justitia et Pax, 2016)
AbstractThis research seeks to analyze how the use of suffrage by a law student voters Atma Jaya Yogyakarta University in legislative and presidential elections in 2014 and the factors that determine the choice. Respondents who gave point of views are all students of the Faculty of Law, University of Atma Jaya Yogyakarta who elected for the first time and have the right to vote because it has been qualified in terms of age. Based on the analysis, it can be concluded that; generally, the use of suffrage showed a fairly high level, compared legislatif election in the legislative elections of use suffrage show the increasing of participation. amounted to 11.62%. However, they found there are quite a lot of voters who do not use their voting rights. Most common reasons which become factor why they did not vote is because it is not registered as a voter, Respondents, whether in using their suffrage in presidential or general election have the same consideration inÂ  determining the choice. where figur candidates (legislative / president) factors was chosen as the most consideration in determining the choice, followed by factors figur and political party who support related to candidates figur in legislative and presidential elevtion have similarities, humble and sociablefollowed by commitment, moral and strictness .Recommendations which can be given, is that it should be increased voter participation in elections as a manifestation of the rights and responsibilities of the people (voters) in maintaining the survival of the nation and the state. Thus, it should be developed political consciousness of society that can be obtained through political education, whether through formal and informal education. Communities should also actively follow and understand information/socialization which are organized by election organizers (General Election Commission), including rules concerning voter registration.Keywords: Use of Suffrage, Beginner Voters, Legislative Election, Presidential Election factors that determine the choice.IntisariPenelitian ini hendak menganalisis bagaimana penggunaan hak pilih oleh pemilih pemula mahasiswa fakultas hukum universitas atma jaya yogyakarta dalam pemilu legislatif dan pemilu presiden tahun 2014 dan faktor-faktor yang menentukan pilihan. Responden yang dimintakan pandangan adalah seluruh mahasiswa Fakultas Hukum Universitas Atma Jaya Yogyakarta yang baru pertama kali memiliki hak pilih karena telah memenuhi syarat dari segi usia. Mendasarkan pada analisis, dapat disimpulkan bahwa; Secara umum penggunaan hak pilih menunjukkan tingkat yang cukup tinggi, peningkatan sebesar 11,62 % merupakan hal cukup positif. Namun demikian masih didapati adanya pemilih yang tidak menggunakan hak pilihnya. Alasan yang paling banyak menjadi faktor tidak menggunakan hak pilih adalah karena tidak terdaftar sebagai pemilih. Responden dalam menggunakann hak pilihnya dalam pemilu legislatif dan pemilu presiden memiliki kesamaan dalam hal pertimbangan yang digunakan sebagai dasar dalam menentukan pilihan. Rekomendasi yang dapat diberikan, adalah bahwa Perlu ditingkatkan partisipasi pemilih dalam penyelenggaraan pemilu sebagai wujud dari hak dan tanggung jawab masyarakat (pemilih) dalam mempertahankan kelangsungan hidup bangsa dan negara. Tingkat partisipasi pemilih yang tinggi juga dapat meningkatkan legitimasi terhadap kekuasaan yang diperoeh dari rakyat melalui pemilu. Untuk itu perlu ditumbuhkan kesadaran politik masyarakat yang dapat diperoleh melalui pendidikan politik, baik melalui pendidikan formal maupun informal. Terkait dengan pemilih yang tidak terdaftar dalam pemilihan umum, masyarakat juga harus secara aktif mengikuti dan memahami informasi/sosialisasi yang dilakukan penyelenggara pemilu (Komisi Pemilihan Umum), termasuk aturan-aturan yang menyangkut pendaftaran pemilih. Kata Kunci: hak pilih,Â  pemilih pemula, Pemilu